Human acute myeloid leukemia CD34+CD38− stem cells are susceptible to allorecognition and lysis by single KIR-expressing natural killer cells - Ulrich Langenkamp; Uwe Siegler; Simon Jörger; Stefan Diermayr; Alois Gratwohl; Christian P. Kalberer; Aleksandra Wodnar-Filipowicz (Haematologica, 2009)
The concept of tumor immunosurveillance has raised prospects for natural killer cell-based immunotherapy of human cancer. The cure of acute myeloid leukemia may depend on eradication of leukemic stem cells, the self-renewing component of leukemia. Whether natural killer cells can recognize and lyse leukemic stem cells is not known. To develop strategies that effectively target acute myeloid leukemia-leukemic stem cells, we investigated anti-leukemic effects of human alloreactive single KIR+ natural killer cells. Natural killer effectors with KIR specificity mismatched with respect to HLA class I allotype of target cells effectively recognized acute myeloid leukemia-leukemic stem cells defined phenotypically as CD34+CD38−, while healthy bone marrow-derived CD34+CD38− hematopoietic stem cells were spared, as demonstrated by cytotoxicity and hematopoietic colony-forming assays. The HDAC inhibitor valproic acid increased the activating NKG2D ligand-dependent lysis of acute myeloid leukemia-CD34+CD38− leukemic stem cells. These results show that alloreactive natural killer cells have the potential to detect and target leukemic stem cells, and thus to improve the treatment outcome in acute myeloid leukemia.